Enhancing Reading Proficiency: An Investigation into the Effectiveness of Think Pair Share and Jigsaw - Laily Anzalina; Ary Setya Budhi Ningrum (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
The aim of this study is to find out whether the Think Pair Share (TPS) method and Jigsaw method are effective for teaching reading comprehension skills to the tenth grade students of SMAN 1 Prambon, East Java. The quasi-experimental design was applied in this study. There were 33 students of X2 as the experimental class which is using Think Pair Share Method and 31 students of X1 as the control class which is using Jigsaw Method. The instruments used are pre-test and post-test. The result of this study proved that the Think Pair Share method and Jigsaw are effective to teach reading comprehension. On the other hand, when comparing which method is more effective between the Think Pair Share Method and the Jigsaw Method for teaching reading, it can be seen from the result that Think Pair Share Method is more effective than the Jigsaw Method in teaching reading comprehension.